PEMODELAN STRATEGIS GREEN-DIGITAL BANKING DALAM IMPLEMENTASI ESG UNTUK KINERJA KEBERLANJUTAN BANK PEMBANGUNAN DAERAH INDONESIA: STUDI EMPIRIS BERBASIS PLS-SEM - Muhammad Alfarizi (Universitas Diponegoro, 2026)
Abstract: Environmental protection has become a major focus due to degradation leading to increased occurrences of extreme natural events. The UN Agenda 2030 emphasizes sustainability goals with the principle of